The District of Columbia and Gun Control Laws: Homicides and Social Impacts - Mbakop, Richard Ghislain (2020)
Abstract The District of Columbia has one of the toughest gun laws in the United States, yet the city has one of the highest homicide rates in the nation and much of this gun violence is concentrated in the southeastern part of the city. The framework for the study was comprised of (a) the psychological theory based on many arguments, such as labeling weapons as symbols of male superiority and power, and (b) the social contract theory. Finding the perceptions about the relationship between gun control laws and homicide rates in Washington D.C. was the essential aim of the study. This qualitative case study examined the perceptions of 8 people relative to the relationship between gun control laws and homicide rates in the southeast section of the District of Columbia. Results revealed that the manufacturing and legal acquisition of firearms did not pose any problem for the participants, given the legitimate purpose of using guns. Rather, owners who use guns to perpetrate violent acts due to ineffective distribution and lack of enforcement of laws, added to gun proliferation pose a serious problem. The findings may be used by policymakers to develop policies in controlling, managing, producing, distributing, and owning guns as well as decreasing gun violence across the nation